Subarachnoid Hemorrhage as a Consequence of Pleomorphic Xanthoastrocytoma: A Case Report. Issue 3 (24th July 2021) - Stone, Lauren E; Goodwill, Vanessa; Wali, Arvin R; Hirshman, Brian; Santiago-Dieppa, David R; Khalessi, Alexander
Abstract: BACKGROUND AND IMPORTANCE: Pleomorphic xanthoastrocytoma (PXA) is a rare World Health Organization (WHO) grade II lesion considered to portend a good prognosis. However, the literature contains several references of serious intracranial hemorrhages associated with PXAs, although the etiology is poorly understood. CLINICAL PRESENTATION: We present the case of a young woman with a Hunt and Hess V, Fisher 4 subarachnoid hemorrhage associated with a right cavernous sinus PXA. The case provides rare baseline angiographic imaging prior to a presenting hemorrhagic event and reveals progressive loss of structural vascular integrity at proximal large vessels. CONCLUSION: This case provides insight into the natural history of this entity, tropism for catastrophic vascular injury, and informs surgical management with an emphasis on preoperative vascular imaging and preparation for proximal vascular control with cervical exposure.